Pollinator sharing between reproductively isolated genetic lineages of Silene nutans - Cornet, Camille; Noret, Nausicaa; Van Rossum, Fabienne (Frontiers in Plant Science, 2022)
High reciprocal pollination specialization leading to pollinator isolation can prevent interspecific pollen transfer and competition for pollinators. Sharing pollinators may induce mating costs, but it may also increase pollination services and pollen dispersal and offer more resources to pollinators, which may be important in case of habitat fragmentation leading to pollination disruption. We estimated pollen dispersal and pollinator isolation or sharing between two reproductively isolated genetic lineages of Silene nutans (Caryophyllaceae), which are rare and occur in parapatry in southern Belgium, forming two edaphic ecotypes. As inter-ecotypic crosses may lead to pollen wastage and inviable progeny, pollinator isolation might have evolved between ecotypes. Silene nutans is mainly pollinated by nocturnal moths, including nursery pollinators, which pollinate and lay their eggs in flowers, and whose caterpillars feed on flowers and seeds. Pollinator assemblages of the two ecotypes are largely unknown and inter-ecotypic pollen flows have never been investigated. Fluorescent powdered dyes were used as pollen analogues to quantify intra- and inter-ecotypic pollen transfers and seeds were germinated to detect chlorotic seedlings resulting from inter-ecotypic pollination. Nocturnal pollinators were observed using infrared cameras on the field, and seed-eating caterpillars were collected and reared to identify nursery pollinator species. No pollinator isolation was found: we detected long-distance (up to 5 km) inter-ecotypic dye transfers and chlorotic seedlings, indicating inter-ecotypic fertilization events. The rare moth Hadena albimacula, a nursery pollinator specialized on S. nutans, was found on both ecotypes, as well as adults visiting flowers (cameras recordings) as seed-eating caterpillars. However, S. nutans populations harbor different abundance and diversity of seed predator communities, including other rare nursery pollinators, suggesting a need for distinct conservation strategies. Our findings demonstrate the efficiency of moths, especially of nursery pollinators, to disperse pollen over long distances in natural landscapes, so to ensure gene flow and population sustainability of the host plant. Seed-predator specificities between the two reproductively isolated genetic lineages of S. nutans, and pollinator sharing instead of pollinator isolation when plants occur in parapatry, suggest that conservation of the host plant is also essential for sustaining (rare) pollinator and seed predator communities.